The Philippine Revolution in the Proceedings of the Berlin Society for Anthropology, Ethnology, and Prehistory from 1897 to 1900: Five Translations - Weston, Nathaniel P.; (Archīum Ateneo, 2013)
This research note presents discussions about and by Filipino revolutionaries in the Proceedings of the Berlin Society for Anthropology, Ethnology, and Prehistory (Verhandlungen der Berliner Gesellschaft für Anthropologie, Ethnologie und Urgeschichte), which were published from 1897 to 1900 in the Imperial German Journal of Ethnology (Zeitschrift für Ethnologie), a periodical produced by the German Society for Anthropology, Ethnology, and Prehistory (Deutsche Gesellschaft für Anthropologie, Ethnologie und Urgeschichte). It contextualizes and translates five communications: two describing the life and work of José Rizal, and three letters from Mariano Ponce, Felipe Agoncillo, Emiliano Riego de Dios, and Vicente Lukban.Keywords: German anthropology • translation • Filipino nationalism • Filipino scholarship • Philippine Revolution